Risk Factors of Central Serous Chorioretinopathy among Nepali Population - Pant, Nayana; Bhatta, Subash; Pant, Suresh Raj (Nepalese Journal of Ophthalmology, 2025)
Introduction: Central Serous Chorio-retinopathy (CSCR) is a common cause of retinal blindness in Nepal. Objective: To identify risk factors of Central Serous Chorio-retinopathy (CSCR) in the Nepali population. Methodology: A case-control study was conducted on patients with CSCR presenting at tertiary eye center of Nepal, from 2019 to 2021. Data on age, gender, ethnicity, stress, axial length, alcohol drinking and other risk factors were collected. Chi-square tests were conducted to find associations between variables and CSCR. Binary logistic regression was utilised to determine the odds of developing CSCR among the cases and to adjust for potential confounders. Wilcoxon Rank Sum test was used to compare means. Result: The study included 145 eyes from 132 cases of CSCR and 145 age- and sex-matched controls. Young adults in the age group of 31-40 years and male gender were significantly associated with CSCR (p<.05). Tharu ethnicity (adjusted OR= 3.3 95% Confidence Interval=1.890-5.444), shorter axial length (adjusted OR= 1.725; 95% CI=1.271-2.342) and alcohol use (adjusted OR=2.779, 95% CI=1.136-6.799) were significantly associated with CSCR. Smoking, stress, inadequate sleep, and night duties were common among CSCR cases but did not reach statistical significance. Conclusion: This is first study in Nepal to report higher prevalence of CSCR in tharu ethnic group. Young adult male, alcohol drinking and short axial length are other significant risk factors of CSCR among Nepali population. Although the study does not establish temporal causation, it underscores need to suspect CSCR in tharu patients presenting with relevant symptoms. Further research is warranted to explore why the tharu population is more susceptible to CSCR.